2012
DOI: 10.3747/co.19.1038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy of Current Clinical Practice of Adjuvant Chemotherapy in Postmenopausal Women with Early-Stage, Estrogen or Progesterone Receptor–Positive, One-To-Three Positive Axillary Lymph Node, Breast Cancer

Abstract: for all women with er/pr+ 1-3 ln+ esbc. There could be a subgroup of those women who do not benefit from adjuvant chemotherapy as expected and who are therefore being overtreated. Further studies with a larger sample size are warranted to confirm our results. KEY WORDSBreast cancer, adjuvant chemotherapy, clinical practice patterns

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Although RCTs remain the gold standard for comparing treatments, patient selection criteria and the lack of flexibility in protocol-specified dose modifications and toxicity management limit the generalizability of the findings to the individual patient (Hahn and Schilsky 2012). The major questions are whether results of RCTs can be applied to ‘real world’ patients (sometimes with medical co-morbidities or borderline organ function), whether they are also reliably for subsets of patients with different clinical characteristics and whether patients nonenrolled in RCTs have a worst outcome than randomized patients (Korn and Freidlin 2012; Braunholtz et al 2001; Peppercorn et al 2004; Hannouf et al 2012; Engstrom et al 2012; Tanai et al 2011). From this point of view, observational retrospective studies are considered alternative good sources of information on the effectiveness of treatments used according to patient and tumor characteristics (Korn and Freidlin 2012; Lyman and Levine 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although RCTs remain the gold standard for comparing treatments, patient selection criteria and the lack of flexibility in protocol-specified dose modifications and toxicity management limit the generalizability of the findings to the individual patient (Hahn and Schilsky 2012). The major questions are whether results of RCTs can be applied to ‘real world’ patients (sometimes with medical co-morbidities or borderline organ function), whether they are also reliably for subsets of patients with different clinical characteristics and whether patients nonenrolled in RCTs have a worst outcome than randomized patients (Korn and Freidlin 2012; Braunholtz et al 2001; Peppercorn et al 2004; Hannouf et al 2012; Engstrom et al 2012; Tanai et al 2011). From this point of view, observational retrospective studies are considered alternative good sources of information on the effectiveness of treatments used according to patient and tumor characteristics (Korn and Freidlin 2012; Lyman and Levine 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey among researchers in the breast cancer field [21] found that the identification of hormone receptor-positive breast cancer patients who might on charged glass slides. After paraffin removal, sections were dehydrated and incubated in 2mM NaCN for 20 minutes and later held in pepsin for an average 30 min followed by denaturation in formamide solution.…”
Section: Tumor Biological Techniquesmentioning
confidence: 99%
“…Although the clinicopathologic presentation of CUP patients may differ from that of patients with CKP, there does not seem to be a major disparity in the response rates and the outcomes between these two patient groups after the primary tumour is defined and tumour-specific therapies are administered [ 29 ]. However, the impact of primary tumour identification via gene expression profiling on clinical outcomes for patients with CUP remains uncertain and difficult to prove in randomized trials because of a combination of ethical, clinical and logistical considerations [ 29 31 ]. Additional clinical evidence is necessary to optimize a precision medicine strategy as a standard of care for patients with CUP.…”
Section: Introductionmentioning
confidence: 99%